Career adapt-abilities scale: psychometric properties in a Lebanese sample - Marques, Cátia (2023)
This study examined the psychometric properties of the Career Adapt-Abilities Scale in a Lebanese sample. The study includes 236 Lebanese citizens (54.2% women; Mage = 30.14). Confirmatory factor analyses indicated that a hierarchical model yielded a good fit, with the CAAS measuring four distinct dimensions that can be combined in a higher-order career adaptability factor in a Lebanese sample. Results showed that the overall CAAS and sub-dimensions were highly reliable. Pearson correlation coefficients demonstrated that the CAAS’ scores were related to those of basic values and life satisfaction. The CAAS constitutes a promising measure to be used in Lebanese career counselling.